A study of the moderating influence of R&D intensity on the family management-firm performance relationship: Evidence from Spanish private manufacturing firms - J. Diéguez-Soto; M. Manzaneque; V. González-García; Teodoro Galache (BRQ Business Research Quarterly, 2019)
This study investigates the moderating influence of R&D intensity on the relationships between family management and firm performance in private firms. The results confirm that R&D intensity reinforces the negative effect of family management on firm performance. More specifically, we obtain that R&D intensity is a statistically significant moderator for those firms having large levels of R&D investment relative to one's industry peers. Likewise, we find that only when taking into account the total effect of R&D, including internal and external R&D, does its interaction with family management has a detrimental effect on firm performance.
Keywords: L25; M12; O32; 650; Family management; Firm performance; Internal and external R&D; R&D intensity